2015
DOI: 10.1111/exd.12606
|View full text |Cite
|
Sign up to set email alerts
|

A putative antipruritic mechanism of the phosphodiesterase‐4 inhibitor E6005 by attenuating capsaicin‐induced depolarization of C‐fibre nerves

Abstract: E6005, a potent, selective phosphodiesterase (PDE) 4 inhibitor, has been developed as a novel topical agent of atopic dermatitis (AD). It has been shown to inhibit itching in patients with AD as well in mouse models. To study the mechanism underlying the anti-pruritic effect of E6005, we examined its effect on the activation of dorsal root ganglion (DRG) neurons associated with the itch sensation. Depolarization of DRG neurons by a transient receptor potential vanilloid 1 (TRPV 1) activator, capsaicin was atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Another important finding is that compared with the vehicle group, the 0.2% E6005 group showed a significant improvement in excoriation, which is consistent with the improvement in the pruritus score. Several antipruritic mechanisms of topical E6005 have been proposed recently: (i) direct inhibition of the PDE4B subtype expressed in dorsal root ganglion neurons; (ii) suppression of the upregulation of skin nerve growth factor levels; and (iii) inhibition of responses to proteinase‐activated receptor 2 stimulation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important finding is that compared with the vehicle group, the 0.2% E6005 group showed a significant improvement in excoriation, which is consistent with the improvement in the pruritus score. Several antipruritic mechanisms of topical E6005 have been proposed recently: (i) direct inhibition of the PDE4B subtype expressed in dorsal root ganglion neurons; (ii) suppression of the upregulation of skin nerve growth factor levels; and (iii) inhibition of responses to proteinase‐activated receptor 2 stimulation …”
Section: Discussionmentioning
confidence: 99%
“…Several antipruritic mechanisms of topical E6005 have been proposed recently: (i) direct inhibition of the PDE4B subtype expressed in dorsal root ganglion neurons; (ii) suppression of the upregulation of skin nerve growth factor levels; and (iii) inhibition of responses to proteinase-activated receptor 2 stimulation. 7,8,22,23 The limitations of this exploratory study include its small sample size, which was not calculated from a statistical viewpoint, the concomitant use of antiallergics, the restricted availability of application sites (the skin of the face and head was not an application site), and the short study period (2 weeks), which might not have allowed adequate assessment of the clinical efficacy of treatment with topical E6005 for chronic AD. Therefore, further trials with larger sample sizes and longer study periods are warranted to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E6005 (RVT-501) is a selective PDE4 inhibitor and has shown antipruritic abilities in mouse models mimicking AD [61][62][63]. E6005 is able to suppress C-fibre depolarization and activation of the dorsal root ganglion through elevation of cAMP levels, thereby exerting an antipruritic effect [62].…”
Section: E6005mentioning
confidence: 99%
“…E6005 is able to suppress C-fibre depolarization and activation of the dorsal root ganglion through elevation of cAMP levels, thereby exerting an antipruritic effect [62]. An early phase I/II study evaluating safety, tolerability, and pharmacokinetics showed no application site adverse event related to treatment and systemic absorption was below the detection limit [64].…”
Section: E6005mentioning
confidence: 99%